Investigating implementation of school health policies through a health equity lens: A measures development study protocol - McLoughlin, Gabriella M.; Walsh-Bailey, Callie; Singleton, Chelsea R.; Turner, Lindsey (Frontiers in Public Health, 2022)
Background School-based policies that ensure provision of nutrition, physical activity, and other health-promoting resources and opportunities are essential in mitigating health disparities among underserved populations. Measuring the implementation of such policies is imperative to bridge the gap between policy and practice. Unfortunately, limited practical, psychometrically strong measures of school policy implementation exist. Few available explicitly focus on the issues of equity and social justice as a key component of implementation, which may result in underassessment of the equity implications of policy implementation. The purpose of this study is to develop equity-focused measures in collaboration with practitioners, researchers, and other key implementation partners that will facilitate evaluation of policy implementation determinants (i.e., barriers and facilitators), processes, and outcomes. Methods We will actively seek engagement from practitioners, researchers, and advocacy partners (i.e., stakeholders) who have expertise in school health policy throughout each phase of this project. We propose a multi-phase, 1-year project comprising the following steps: (1) selection of relevant constructs from guiding frameworks related to health equity and implementation science; (2) initial measure development, including expert feedback on draft items; (3) pilot cognitive testing with representatives from key target populations (i.e., school administrators, teachers, food service staff, and students and parents/guardians); and (4) measure refinement based on testing and assessment of pragmatic properties. These steps will allow us to establish initial face and content validity of a set of instruments that can undergo psychometric testing in future studies to assess their reliability and validity. Discussion Completion of this project will result in several school policy implementation measurement tools which can be readily used by practitioners and researchers to evaluate policy implementation through a health equity lens. This will provide opportunities for better assessment and accountability of policies that aim to advance health equity among school-aged children and their families. Trial registration Open Science Framework Registration doi: 10.17605/OSF.IO/736ZU.